Valoração econômica da função ambiental de suporte relacionada às atividades de turismo, Brotas, SP. - Oliveira Junior, Arnaldo Freitas de (Universidade Federal de São Carlos, 2003)
The adventure tourism in Brotas city, Brazil, is an alternative economical viable contributing to the development socioeconomic of city. The resources natural the exist in Brotas they are the base for the practice of several sports as cannoning, mountain bike, boia-cross , and others. This work have objective to estimate valuate of benefits socioeconomic flowed of resources natural s for the activities of adventure sports. The used method was use direct of resources natural. The environmental valuation became efficient for estimate the several goods and services coming of use of elements natural s in Brotas city. However, the municipal district request one environmental planning addressed to management of the tourism so that actives association to the tourism promote the development sustainable in Brotas city.
Economics Valuation of Functions Environmental of Support associates in activity of Adventure Tourism. Case of study: Brotas, SP, BRAZIL
Keywords: Ecologia; Economia ecológica; Ecoturismo; Turismo de aventura; Política ambiental; Environmental valuation; Ecologic economic; Adventure tourism; Ecotourism; Sustainable development; CIENCIAS BIOLOGICAS::ECOLOGIA